2008
DOI: 10.1186/1471-2164-9-110
|View full text |Cite
|
Sign up to set email alerts
|

Search for the genes involved in oocyte maturation and early embryo development in the hen

Abstract: Background: The initial stages of development depend on mRNA and proteins accumulated in the oocyte, and during these stages, certain genes are essential for fertilization, first cleavage and embryonic genome activation. The aim of this study was first to search for avian oocyte-specific genes using an in silico and a microarray approaches, then to investigate the temporal and spatial dynamics of the expression of some of these genes during follicular maturation and early embryogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 66 publications
2
27
0
1
Order By: Relevance
“…Dazl, however, is expressed in both male and female germ cell. Its homolog has been identified in model organisms including human (Nishi et al, '99;Brekhman et al, 2000), mouse (Ruggiu et al,'97), chicken (Yamamoto et al, 2007;Elis et al, 2008), Xenopus (Houston et al,'98), axolotl (Johnson et al, 2001), newt (Tamori et al, 2004), zebrafish (Maegawa et al,'99) and medaka (Xu et al, 2007). Loss-of-function experiments demonstrated that the Dazl gene functions in both meiosis and normal germ cell development process in several species (Ruggiu et al, '97;Houston and King, 2000b).…”
mentioning
confidence: 99%
“…Dazl, however, is expressed in both male and female germ cell. Its homolog has been identified in model organisms including human (Nishi et al, '99;Brekhman et al, 2000), mouse (Ruggiu et al,'97), chicken (Yamamoto et al, 2007;Elis et al, 2008), Xenopus (Houston et al,'98), axolotl (Johnson et al, 2001), newt (Tamori et al, 2004), zebrafish (Maegawa et al,'99) and medaka (Xu et al, 2007). Loss-of-function experiments demonstrated that the Dazl gene functions in both meiosis and normal germ cell development process in several species (Ruggiu et al, '97;Houston and King, 2000b).…”
mentioning
confidence: 99%
“…Trappins have been identified as potential treatment for emphysema, because trappin 2 is able to reduce emphysematous changes by increasing granulocyte colony-stimulating factor (G CSF) (Janelle et al, 2006). TRAP6 was identified as an oocyte gene in our previous study (Elis et al, 2008). Indeed, according to microarray experiments, this gene was more highly expressed in GDR at the F1 stage than in granulosa cells at the same stage or in GDR at the ovulation stage.…”
Section: Discussionmentioning
confidence: 93%
“…Germinal disc regions (GDR) were collected as previously described (Malewska and Olszanska, 1999;Elis et al, 2008) from different preovulatory follicles (F1-F3), from recently (1-5 min) ovulated oocytes and from early embryos at 6.5, 24, and 48 hr postovulation. The GDR from preovulatory follicles consisted of the germinal disc and of the overlying layer of GCs, because GD and overlying GCs cannot be separated (Elis et al, 2008). The 6.5 and 24 hr stages of embryo development correspond to stages I and X of the Eyal-Giladi and Kochav (1976) classification, respectively.…”
Section: Collection Of Tissue Oocytes and Embryosmentioning
confidence: 99%
See 2 more Smart Citations